HEMAGGLUTINATION AND ANTIGENIC PROPERTIES OF AVIBACTERIUM PARAGALLINARUM ISOLATES RECOVERED IN THE RUSSIAN FEDERATION AND REPUBLIC OF BELARUS - A. V. Potehin; V. A. Yevgrafova; D. B. Andreychuk (Ветеринария сегодня)
The paper demonstrates examination results of antigenic properties of Avibacterium paragallinarum reference strain and ten isolates thereof recovered in the Russian Federation and Republic of Belarus. Nine isolates and the reference strain demonstrated type L hemagglutinin (thermoliable, trypsin-sensitive, active against fresh and glutaraldehyde-treated RBC). One isolate was marked by type Hl hemagglutinin (thermoliable, trypsin-resistant, active only against glutaraldehydetreated RBC). The reference strain antigen proved to be inagglutinable by homologous antiserum, and unable to agglutinate RBCs due to hyaluronic acid in the capsular substance. Serological and hemagglutination non-reactivity was removed through the cell treatment with hyaluronidase. The agglutination test demonstrated that seven out of ten tested isolates belonged to the same serological group; herewith, the proportion of the bilateral antigenic relatedness amounted to ≥78.4%. HI results demonstrated ≥92.6% antigenic relatedness of the tested isolates being indicative of the fact that they belonged not only to the same serological group but also to the same serotype. No serological relatedness was identifed between the tested isolates and reference strain of serogroup A both using agglutination test (≤23.6%) and HI (≤12.2%). Polymerase chain reaction demonstrated that all the isolates recovered in the Russian Federation and Republic of Belarus in 2014-2016 belonged to serogroup B.